Characterizing iconic gesture during narratives in chronic traumatic brain injury recovery - Urena, Katelyn; Stark, Brielle C. (Frontiers in Human Neuroscience, 2024)
It is known that co-speech hand gestures increase and supplement speech in individuals with language impairment after brain injury, e.g., post-stroke aphasia. Traumatic Brain Injury (TBI) provides a unique avenue to evaluate gestures as TBI often presents with both anomia (word-finding impairments) and cognitive impairments, resulting in a cognitive-communicative disorder. However, there is a great need for evaluation of gestures in TBI during typical spontaneous speech and across the recovery trajectory (from sub-acute to chronic stages). In a large population (N=54) of persons with moderate-severe TBI, who were examined at three months post-TBI whilst telling a procedural narrative ("how to make a sandwich"), we examined three aims: (1) characterize the extent to which adults with moderate-severe TBI produce iconic gestures; (2) identify the extent to which language impairment relates to iconic gesturing in TBI; and (3) characterize the extent to which iconic gesturing changes across TBI recovery. In a subpopulation (Group 1, N=14) who were examined at three-and 24months (sub-acute and substantially chronic), and in a smaller subpopulation (Group 2, N=6) who had data for five timepoints (three-, six-, nine-, 12-, and 24-months), we used paired tests to examine and characterize longitudinal changes in iconic gesturing. The large group analysis suggested that individuals with TBI use iconic gesture during narrative, which take several different iconic forms (e.g., enacting use of an object), and that a minority employed gestures that supplemented (added to, disambiguated, or replaced) speech. The subpopulation analyses suggested that participants did not produce iconic gestures significantly differently across the two-year recovery timeframe. Case examination of a participant with moderate-severe aphasia suggested a relationship between language impairment and gesture, with this individual producing the highest proportion of supplemental gesturing of the entire group. This finding aligns with research from the post-stroke aphasia field. Broadly, this study significantly extends prior research on the relationship between gesturing, language, and brain injury.